The Impact of Interpersonal Communication and Organizational Climate on Early Childhood Education Teacher Performance: A Path Analysis in Pandeglang Regency - Moch Faisal; Elis Haerani; Herni Srirahayu; Devi Fatwanti; Zakaria Syafei; Rijal Firdaos; Eka Sri Mulyani (CV. Edujavare Publishing, 2026)
This study aims to comprehensively analyze and describe the impact of interpersonal communication and organizational climate on the performance of Early Childhood Education (PAUD) teachers in the Pandeglang region. This study departs from the urgency of understanding how interactions between educators and perceptions of the work environment can influence professionalism and work effectiveness. By adopting a causal associative quantitative research design, this study uses path analysis techniques to examine the relationship between variables. The study population involved 102 PAUD teacher respondents selected through cluster random sampling techniques. All data collected using survey instruments were analyzed and analyzed in depth using the Analysis of Moment Structural (AMOS) program version 21. The results show that there is a direct and significant influence of interpersonal communication on organizational climate, as well as a positive influence of organizational climate on the performance of PAUD teachers in the Pandeglang region. Empirical findings confirm that organizational climate plays a major role in achieving performance, with a correlation coefficient of 0.612 and a path coefficient of 0.442. This indicates that the synergy between open interpersonal communication and a conducive organizational climate is a fundamental prerequisite for improving educator professionalism. Managerial transformation based on strengthening the work climate has been proven to create a more productive and competitive educational environment.